Clinical and pathologic features of primary membranous nephropathy in Turkey: a multicenter study by the Turkish Society of Nephrology Glomerular Diseases Working Group. Issue 1 (31st December 2022) - Yildiz, Abdulmecit; Ulu, Sena; Oruc, Aysegul; Ucar, Ali Riza; Ozturk, Savas; Alagoz, Selma; Eren, Necmi; Kocyigit, Ismail; Koksal Cevher, Simal; Haras, Ali Burak; Sumnu, Abdullah; Arinsoy, Turgay; et al.
Abstract: Background: We aimed to evaluate the features of primary membranous nephropathy (MNP) in Turkish people. Methods: This is a retrospective analysis of patients with biopsy-proven primary MNP. We obtained the data collected between 2009 and 2019 in the primary glomerulonephritis registry of the Turkish Society of Nephrology Glomerular Diseases Study Group (TSN-GOLD). Patients with a secondary cause for MNP were excluded. Clinical, demographic, laboratory, and histopathological findings were analyzed. Results: A total of 995 patients with primary MNP were included in the analyses. Males constituted the majority (58.8%). The mean age was 48.4 ± 13.9 years. The most common presentation was the presence of nephrotic syndrome (81.7%) and sub nephrotic proteinuria (10.3%). Microscopic hematuria was detected in one-third of patients. The median estimated glomerular filtration rate (eGFR) was 100.6 mL/min/1.73 m 2 (IQR, 75.4–116.3), and median proteinuria was 6000 mg/d (IQR, 3656–9457). Serum C3 and C4 complement levels were decreased in 3.7 and 1.7% of patients, respectively. Twenty-four (2.4%) patients had glomerular crescents in their kidney biopsy samples. Basal membrane thickening was detected in 93.8% of cases under light microscopy. Mesangial proliferation and interstitial inflammation were evident in 32.8 and 55.9% of the patients, respectively. The most commonly detected depositions were IgG (93%), C3 complement (68.8%), and kappa and lambda immunoglobulin light chains (70%). Although renal functions were normal at presentation, vascular, interstitial, and glomerular findings were more prominent on biopsy in hypertensive patients. No significant effect of BMI on biopsy findings was observed. Conclusions: Despite some atypical findings, the main features of primary MNP in Turkey were similar to the published literature. This is the largest MNP study to date conducted in Turkish people.